'Shockvertising': An exploratory investigation into attitudinal variations and emotional reactions to shock advertising. Issue 2 (21st March 2013) - Parry, Sara; Jones, Rosalind; Stern, Philip; Robinson, Matthew; Hassan, Louise M.; Michaelidou, Nina
ABSTRACT This study compares the reactions towards shock advertising in for‐profit (FP) and not‐for‐profit (NFP) organizations. Although the use of shocking advertisements is a growing phenomenon, the findings regarding the effectiveness of such advertisements remain mixed. Moreover, there is little consideration of the use of these tactics in different organizational contexts and the effect on the consumer. A qualitative methodology was adopted and included the use of focus groups to explore the attitudes and emotional reactions of a range of individuals. The shocking images from both the NFP and FP organizations were deemed successful at capturing the audience's attention. Some images were more 'shocking' than others, whereas some were more effective at drawing attention to the product or the cause. Importantly, the use of shock advertising was perceived to be justifiable in the NFP sector but much less so in the FP sector. Reactions were somewhat influenced by both religion and gender; however, it was apparent that this sample were inherently more accepting of shock advertising than expected. Despite the apparent immunity of today's youth to shock tactics, this study found that there are still themes that are considered inappropriate in FP and NFP sectors; these include the use of religious taboos or morally offensive images. Copyright © 2013 John Wiley & Sons, Ltd.